Dichotomous dynamics of magnetic monopole fluids - Hsu, C-C; Takahashi, H; Jerzembeck, F; Dasini, J; Carroll, C; Dusad, R; Ward, J; Dawson, C; Sharma, S; Luke, GM; Blundell, SJ; Castelnovo, C; et al. (National Academy of Sciences, 2024)
A recent advance in the study of emergent magnetic monopoles was the discovery that monopole motion is restricted to dynamical fractal trajectories [J. N. Hallén et al., Science 378, 1218 (2022)], thus explaining the characteristics of magnetic monopole noise spectra [R. Dusad et al., Nature 571, 234 (2019); A. M. Samarakoon et al., Proc. Natl. Acad. Sci. U.S.A. 119, e2117453119 (2022)]. Here, we apply this novel theory to explore the dynamics of field-driven monopole currents, finding them composed of two quite distinct transport processes: initially swift fractal rearrangements of local monopole configurations followed by conventional monopole diffusion. This theory also predicts a characteristic frequency dependence of the dissipative loss angle for AC field–driven currents. To explore these novel perspectives on monopole transport, we introduce simultaneous monopole current control and measurement techniques using SQUID-based monopole current sensors. For the canonical material Dy2Ti2O7, we measure Φ(t), the time dependence of magnetic flux threading the sample when a net monopole current J(t) = Φ̇ (t)∕0 is generated by applying an external magnetic field B0(t). These experiments find a sharp dichotomy of monopole currents, separated by their distinct relaxation time constants before and after t ~600 μs from monopole current initiation. Application of sinusoidal magnetic fields B0(t) = Bcos(t) generates oscillating monopole currents whose loss angle ( f ) exhibits a characteristic transition at frequency f ≈ 1.8 kHz over the same temperature range. Finally, the magnetic noise power is also dichotomic, diminishing sharply after t ~600 μs. This complex phenomenology represents an unprecedented form of dynamical heterogeneity generated by the interplay of fractionalization and local spin configurational symmetry.